Symptomatic Management of Febrile Illnesses in Children: A Systematic Review and Meta-Analysis of Parents' Knowledge and Behaviors and Their Evolution Over Time - Bertille, Nathalie; Purssell, Edward; Hjelm, Nils; Bilenko, Natalya; Chiappini, Elena; de Bont, Eefje G. P. M.; Kramer, Michael S.; Lepage, Philippe; Lava, Sebastiano A. G.; Mintegi, Santiago; Sullivan, Janice E.; Walsh, Anne; et al. (Frontiers in Pediatrics, 2018)
Recommendations to guide parents' symptomatic management of febrile illnesses in children have been published in many countries. The lack of systematic appraisal of parents' knowledge and behaviors and their evolution over time precludes an analysis of their impact and identification of targets for future educational messages. We systematically searched for studies published between 1980 and 2016 that reported a quantitative evaluation of knowledge and behaviors of >50 parents for managing fever in children. We used MEDLINE and tracked related articles, citations and co-authors personal files. Study selection and data extraction were independently performed by 2 reviewers. For each item of knowledge and behaviors, we calculated mean frequencies during the first and last quinquennials of the studied period and assessed temporal trends with inverse-variance weighted linear regression of frequencies over years. We observed substantial methodological heterogeneity among the 62 included articles (64 primary studies, 36,791 participants, 30 countries) that met inclusion criteria. Statistically significant changes over time were found in the use of rectal (98% to 4%) and axillary temperature measurement (1% to 19%), encouraging fluid intake (19% to 62%), and use of acetylsalicylic acid (60% to 1%). No statistically significant change was observed for the accurate definition of fever (38% to 55%), or the use of acetaminophen (91% to 92%) or ibuprofen (20% to 43%). Parents' knowledge and behaviors have changed over time but continue to show poor concordance with recommendations. Our study identified future targets for educational messages, including basic ones such as the definition of fever.